2021
DOI: 10.7759/cureus.15066
|View full text |Cite
|
Sign up to set email alerts
|

Brugada Pattern Phenocopy Induced by Diabetic Ketoacidosis

Abstract: Brugada syndrome is a congenital cardiac channelopathy characterized by ST-segment elevation (≥2 mm) and subsequent inverted T wave in a minimum of two right precordial leads (Brugada type 1 ECG [electrocardiogram] pattern) on ECG. Brugada syndrome is estimated to be responsible for 4%-12% of all sudden cardiac deaths and up to 20% in patients with structurally normal hearts. Development of a temporary Brugada pattern, known as Brugada phenocopy, has been observed in individuals presenting with reversible unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…Landa et al reported a demonstrative type 1 Brugada pattern presenting with diabetic ketoacidosis, hyponatremia, and hyperkalemia in a follow-up patient diagnosed with type 1 diabetes mellitus. In their presentation, the authors demonstrated that the elimination of metabolic and electrolyte disturbances produced a dramatic improvement in ECG findings [ 16 ]. Multiple electrolyte disturbances are not always necessary for BrP.…”
Section: Discussionmentioning
confidence: 99%
“…Landa et al reported a demonstrative type 1 Brugada pattern presenting with diabetic ketoacidosis, hyponatremia, and hyperkalemia in a follow-up patient diagnosed with type 1 diabetes mellitus. In their presentation, the authors demonstrated that the elimination of metabolic and electrolyte disturbances produced a dramatic improvement in ECG findings [ 16 ]. Multiple electrolyte disturbances are not always necessary for BrP.…”
Section: Discussionmentioning
confidence: 99%